Efeito de técnicas de pigmentação pré- e/ou pós-sinterização no comportamento mecânico de uma zircônia translúcida para restaurações monolíticas - Souza, Luiza Freitas Brum (2022)
The present dissertation aimed to characterize the effect of pre- (shading) and/or post- (staining) sintering pigmentation techniques to provide a Vita Classical A2 color on the mechanical properties of a 4YSZ ceramic (IPS e.max ZirCAD). In the first article, different shading techniques were explored. For such, 4YSZ discs (Ø=10mm and 1mm thickness) were allocated into 4 groups: Manufacturer: factory pigmentation; Brush: brush technique; Immersion: immersion technique; Control: control condition without pigment. Afterwards, these were adhesively luted to dentin analogue (Ø=10mm and 2.5mm thickness) using resin cement. The assemblies (n=15) were subjected to a fatigue test (stepstress) and fractography, roughness, topography, grain size and crystalline phase content analyses. No differences in mechanical behavior were observed between the Control group and the pigmented specimens. However, the Brush group showed lower mechanical behavior compared to the Manufacturer group. No differences were observed regarding the Weibull modulus. The specimens from the Brush group showed greater roughness, in addition to greater grain size compared to the other conditions. No m-phase content was identified for the analyzed groups. Therefore, the shading techniques used do not affect the mechanical fatigue properties of an adhesively luted 4YSZ negatively. In the second study, shading and staining techniques were compared in an isolated scenario. For such, 4YSZ discs were prepared (ISO 6872–2015) and allocated into 5 groups: Ctrl: no pigmentation; Manuf: factory pigmentation; Brush: shading (brush technique); Stain: staining; Brush+Stain: combination of techniques. The discs were submitted to a biaxial flexural fatigue testing (piston-on-three-balls) and to fractography, topography and roughness analyses. The Stain group showed lower mechanical behavior than all the others. Stain and Brush+Stain techniques induced inferior mechanical behavior to the Ctrl group. The Brush group was similar to the Ctrl group and presented a lower Weibull modulus than the other groups. Uniformly sized zirconia crystals were observed in Ctrl, Manuf and Brush, and a glassy surface in Stain and Brush+Stain. The staining technique promoted greater roughness. Thus, the pigmentation techniques cause a detrimental effect on the mechanical fatigue properties of 4YSZ, except for the Brush technique. Despite this, Brush presents great variability in mechanical performance. The same techniques were evaluated in the third study, in which the discs (Ø=10mm and 1mm thickness) were adhesively luted to dentin analogue discs (Ø=10mm and 2.5mm thickness), submitted to a fatigue test (step-stress) and fractography, topography and roughness analyses. No influence of the pigmentation techniques was observed in relation to the mechanical behavior. Despite this, the Brush+Stain technique induced inferior mechanical performance compared to Stain. No differences were observed in the Weibull modulus. The staining technique promoted greater roughness. Uniformly sized zirconia crystals were observed in Ctrl, Manuf and Brush, and a glassy surface in Stain and Brush+Stain. Thus, pigmentation techniques do not negatively affect the mechanical fatigue properties of 4YSZ ceramic adhesively luted onto dentin analogue.